2022
DOI: 10.1016/j.jds.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of domiciliary dental care from a university hospital: A retrospective review of the patients and performed treatments in central Taiwan from 2010 to 2020

Abstract: Background/purpose People who suffer with chronic illness, functional impairment, or cognitive impairment are not easily to visit dental clinics. Domiciliary dental care (DDC) can provide the feasible alternative for these clients. In this study, we first reported the DDC services from a university hospital in central Taiwan from 2010 to 2020. Materials and methods This retrospective study collected the DDC data from Department of Dentistry, Chung Shan Medical Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…DDC services were dominated by the elderly living in nursing homes, the home-dwelling and care-dependent elderly, and school-aged children (Table 2). Included in this study Not relevant Excluded as not a research article [9], [7], [11], [8], [12], and [13].…”
Section: Advancement Of Ddcmentioning
confidence: 99%
See 2 more Smart Citations
“…DDC services were dominated by the elderly living in nursing homes, the home-dwelling and care-dependent elderly, and school-aged children (Table 2). Included in this study Not relevant Excluded as not a research article [9], [7], [11], [8], [12], and [13].…”
Section: Advancement Of Ddcmentioning
confidence: 99%
“…Dentists and dental hygienists visit patients in their residences, such as homes or nursing homes, or even schools to prevent or treat oral health problems. Generally, DDC treatment received by the age group <60 is scaling, while the age group ≥60 is tooth extraction treatments [7]. The DDC program was reported to be favored by individuals with limited mobility, making it easier for them to access dental care [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking Taiwan as an example, the proportion of people aging over 65 has been estimated to reach 20% by the end of 2025 [ 7 ], indicating that residents and dentists are coming up against burdens of a super-aged society. In a retrospective review of data on social demographics, geographic locations, place of residence, grade of disability, and type of dental treatments through 2444 visits of 419 patients who received DDC between 2010 and 2020, it was demonstrated that efforts by healthcare organizations in policies and education were warranted to promote DDC [ 8 ]. As such, the purpose of this study was to evaluate a series of continuing medical education (CME) courses on DDC provided by a tertiary medical center and demonstrating center of DDC in Taiwan, and the socio-political impact of the CME modules [ 9 ].…”
mentioning
confidence: 99%
“…In previous decades, not only were dental professionals faced with a lack of experience in DDC, but also dental students were not aware of DDC due to a lack of courses and training, thus leading insufficient access to DDC for medically compromised patients. As such, governmental efforts have been paid in recent years to provoke the awareness of DDC among dentists, nurses, dental assistants, and nursing aides, including the implementation of CME lessons on DDC; in particular, dentists providing DDC have been required to complete CME lessons on DDC since 2015 by the government, for which the Taiwan Dental Association and a total of seven tertiary medical centers have been taking initiative to organize education series on DDC for both dentists and dental students [ 8 ]. Per the implementation of CME series on DDC, it was observed in this study that there was an increasing number of healthcare professionals participating in DDC, including both those in hospitals and those who were PCPs.…”
mentioning
confidence: 99%